Concomitant spuriously elevated white blood cell count, a previously underestimated phenomenon in EDTA-dependent pseudothrombocytopenia. (3rd October 2015) - Xiao, Yufei; Xu, Yang
Abstract: The proportion and potential risk of concomitant spuriously elevated white blood cell count (SEWC) are underestimated in ethylenediaminetetraacetic acid (EDTA)-dependent pseudothrombocytopenia (PTCP). The proportion, kinetics and prevention of SEWC remain poorly understood. A total of 25 patients with EDTA-dependent PTCP were enrolled in this study. With the hematology analyzer Coulter LH 750, we determined the time courses of WBC count, WBC differential and platelet count in EDTA- and sodium citrate-anticoagulated blood, respectively. Blood smears were prepared to inspect the presence of platelet clumps using light microscopy. The effect of automatic instrumental correction on the extent of SEWC was evaluated. The proportion of SEWC was 92% in EDTA-dependent PTCP and 73.9% of SEWCs were within the normal range. The development of SEWC was time-dependent, and neutrophils and lymphocytes were the main subpopulations involved in SEWC. A strong and significant correlation ( r  = 0.9937, p  < 0.001) was found between the increased WBC count and the decreased platelet count. Both corrected and uncorrected WBC counts at 15 minutes or later after blood collection in EDTA were significantly higher than their basal counts, respectively, p  < 0.05. Interestingly, in citrated blood, WBC counts after blood collection were not significantly different from its basal counts, p  > 0.05. A high proportion of concomitant SEWCs, which are mainly within normal range, are present in patients with EDTA-dependent PTCP. Proper interpretation of SEWC is crucial to avoid clinic errors. SEWC develops in a time-dependent pattern, although the Coulter LH 750 only partly mitigates the extent of SEWC, sodium citrate is able to effectively prevent SEWC.